Compreensão leitora de memes: uma proposta de ensino da carnavalização para alunos do 9º ano - Cavalcante, Keziane Fernandes (2023)
Our research aims at improving the reading comprehension of carnivalized memes, by students of the 9th grade of Elementary School, through reading activities based on a dialogical model interposed by the application of the didactic itinerary, based on the format of the itinerary by Dolz, Lima and Zani (2020), aiming at improving reading comprehension skills that will allow a more solid understanding of irony, criticism and implicit information in this type of text, thus promoting the development of students' critical sense. We have theoretically based the reading in the perspective of some authors, such as: Rojo (2004), Antunes (2009), Kleiman (2000), Kato (2005), Smith (1991), Marcondes (2010) among others. In our work, we have used assumptions from the Dialogic Theory of Discourse (DDT), coined by Bakhtin and the Circle, particularly regarding the notion of carnivalization and the assumptions of reading from the perspective of multiliteracy, to investigate and to develop reading comprehension in carnivalized texts such as certain memes. We have approached the carnivalized meme discursive genre for reproducing social themes and showing questions about current issues within society. We believe that researches of this nature contribute to the teaching of reading, since many elementary school students (final years) have difficulties in understanding explicit and mainly implicit information in the texts they read, as well as they do not develop a critical position that leads them to debate and to challenge cultural supremacy by reading and analyzing texts in the classroom and beyond. We believe that basing ourselves on the conceptions of carnivalization, when approaching memes in the classroom, is productive, as it makes it possible to form a critical subject, that is, a subject capable of understanding the oppressor-oppressed relationship, and, through carnivalized laughter, analyzing important social issues. By choosing a carnivalesque vision in the reading classes, we tense to highlight the dominance of power and the stigmas generated by those who are subjugated to the ones in power. In the data analysis chapter, we present the results and analyzes of the application of some activities of the didactic itinerary, confirming the efficiency of the proposed activities in relation to the development of criticity of the students. We suggest, therefore, that we can promote a look at the classroom with this carnivalesque conception, in which it is plausible to analyze the social relations established in the world in a different way since the invalidation of hierarchical relations places the subject in a condition of equivalence.